1974
DOI: 10.1159/000466717
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic A-Like Receptor Sites in Human Erythrocyte Glycoproteins: Proposed Nature of Tn-Antigen

Abstract: Periodate oxidation and Smith degradation of desialized human erythrocyte glycoproteins lead to an almost complete destruction of galactose and some loss of galactosamine and glucosamine. Neutral sugar and hexosamine content of native MN substances are only slightly influenced by periodate oxidation. Destruction of galactose is accompanied by an uncovering of A-like receptor sites detectable by agglutinins from plants and snails, which are directed against terminal N-acetylgalactosamine. From the specificity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 10 publications
(14 reference statements)
3
36
0
2
Order By: Relevance
“…In addition to GSLs indicated to be associated with CSCs in this study, the following were found to be highly expressed in human cancer but either absent or present in negligible amounts in normal cells/tissues: (i) blood group A-like antigens expressed in tumor cells of blood group O or B patients [the structure is GalNAcα1-O-Ser/Thr, termed Tn (63)(64)(65); (ii) sialyl 2-6Tn antigen [i.e., NeuAcα2-6GalNAcα1-O-Ser/Thr (66)]; and (iii) extended type-I antigen [i.e., Le a on Le a (67) or Le b on Le a (68,69)]. Whether these glycan structures are somehow associated with CSCs is an interesting point for future studies.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to GSLs indicated to be associated with CSCs in this study, the following were found to be highly expressed in human cancer but either absent or present in negligible amounts in normal cells/tissues: (i) blood group A-like antigens expressed in tumor cells of blood group O or B patients [the structure is GalNAcα1-O-Ser/Thr, termed Tn (63)(64)(65); (ii) sialyl 2-6Tn antigen [i.e., NeuAcα2-6GalNAcα1-O-Ser/Thr (66)]; and (iii) extended type-I antigen [i.e., Le a on Le a (67) or Le b on Le a (68,69)]. Whether these glycan structures are somehow associated with CSCs is an interesting point for future studies.…”
Section: Discussionmentioning
confidence: 91%
“…(Uhlenbruck et al, 1969) and N-acetyl-Dgalactosamine (Dahr et al, 1974) respectively, were used. The histochemical studies were performed on formaldehydefixed tissue sections from 75 patients, as previously described (Klein et al, 1978(Klein et al, , 1979.…”
mentioning
confidence: 99%
“…Tn-positive cells were initially detected on day 3 of the second phase, and increased during erythroid maturation. Serological and biochemical evidence has shown that N-acetyl-D-galactosamine, when covalently bound to erythrocyte surface sialoglycoproteins, glycophorin A and glycophorin B by an alkali-labile O glycosidic linkage, is the chief structural determinant of Tn specificity (Dahr et al, 1974;Vainchenker et al, 1982;Springer and Desai, 1985). Previously we have demonstrated the expression of glycophorin A in erythroid cells on day 3 of the second phase using the liquid culture system (Wada et al, 1990).…”
Section: Discussionmentioning
confidence: 96%
“…This disorder may be associated with a mild hemolytic anemia, leukopenia, or thrombocytopenia, but has also been described in some acute leukemias or myeloproliferative diseases (Bird et al, 1976;Baldwin et al, 1979;Ness et aI., 1979;Vainchenker et al, 1985). The biochemical basis of Tn activation is now well characterized and corresponds to the exposure of an N-acetylgalactosamine residue carried by cell surface glycoproteins, which arises from a selective loss of a 3-/~-D-galactosyltransferase activity in Tn-positive cells (Dahr et al, 1974;Cartron et al, 1978aCartron et al, , 1978bCartron et al, , 1979.…”
Section: Introductionmentioning
confidence: 96%